A modified boron nitride and its preparation method, and wear-resistant coating

By performing a sulfonate molecular link branch on the surface of the boron nitride, the problem of reunioning boron nitride in the polymer matrix is ​​solved, its dispersability and lubrication effect are improved, and the friction coefficient and wear rate of wear -resistant coating are reduced Essence

CN117586662BActive Publication Date: 2025-01-21JIHUA LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311554367.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2025-01-21
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

Hexagonal boron nitride is prone to agglomeration in polymer matrix, resulting in reduced mechanical properties of the material and lubrication failure, limiting its practical application.

Method used

By performing a ball milling grafting reaction between boron nitride and a compound containing a sulfonic acid active group, a modified boron nitride with a surface chemically grafted with a sulfonic acid molecular chain is prepared. The method includes the mass ratio of boron nitride to sodium polystyrene sulfonate being between 1: (0.5-2), mechanical chemical peeling and chemical grafting through high-energy ball milling.

Benefits of technology

The surface-grafted molecular chain of modified boron nitride effectively reduces the agglomeration of boron nitride, improves its dispersion in the polymer matrix and compatibility with the matrix, and reduces the friction coefficient and wear of the wear-resistant coating. efficiency, improving the lubrication effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004560562850000111
    Figure BDA0004560562850000111
  • Figure BDA0004560562850000121
    Figure BDA0004560562850000121
  • Figure HDA0004560563000000011
    Figure HDA0004560563000000011
Patent Text Reader

Abstract

The present invention relates to a modified boron nitride and a preparation method thereof, and a wear-resistant coating. The preparation method of modified boron nitride comprises: 3 ‑ ) active group molecular chain compound by ball milling to carry out grafting reaction to prepare modified boron nitride; wherein the mass ratio of boron nitride to the compound is 1: (0.5-2). Modified boron nitride is prepared by grafting sulfonic acid (-SO 3 ‑ ) active group, its molecular chain contains a large number of sulfonic acid groups, which reduces the friction coefficient and wear rate of the wear-resistant coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of material technology, and in particular to a modified boron nitride and a preparation method thereof, and a wear-resistant coating. Background Art

[0002] Hexagonal boron nitride has good thermal stability, thermal conductivity and chemical inertness, and is a solid lubricant additive with excellent performance. However, it is very easy to agglomerate in the polymer matrix, which not only reduces the mechanical properties of the material but also causes lubrication failure, which greatly limits the practical application of boron nitride.

[0003] The layered structure of hexagonal boron nitride has atomic-level thickness, ultra-low shear strength between layers, high specific surface area, and surface chemical stability. Nitrogen atoms and boron atoms in the same atomic layer of hexagonal boron nitride are bonded by covalent bonds to form a single-layer structure with high modulus and high strength; the low shear resistance between adjacent atomic layers makes the atomic layers easy to slide; the high specific surface area makes them easily adsorbed onto the contact surface, thereby preventing direct contact between the friction pairs. Therefore, the lubrication performance of hexagonal boron nitride is significantly better than that of traditional lubricating materials.

[0004] However, due to its high chemical stability and the existence of van der Waals forces between layers, hexagonal boron nitride is very easy to irreversibly aggregate in the polymer matrix. Agglomerated hexagonal boron nitride causes defects in the polymer, which not only reduces the mechanical properties of the material, but also leads to lubrication failure, which greatly limits the practical application of hexagonal boron nitride. Chemical modification of hexagonal boron nitride can improve the dispersion of two-dimensional materials in the polymer matrix, improve the interface with the matrix, and enhance the lubrication effect. For example, the surface modification of boron nitride (BN) with epicatechin effectively improves the agglomeration phenomenon of BN in the epoxy resin matrix; by grafting sulfonated polydopamine on the surface of boron nitride, the friction coefficient and wear rate of the epoxy resin coating are significantly reduced. However, the existing reported processing technology is complicated and not economical, which is not conducive to industrial application. In view of this, seeking a simple, efficient and economical two-dimensional material boron nitride surface modification technology still faces huge challenges. Summary of the invention

[0005] In order to solve at least one of the above technical problems, the present disclosure provides a modified boron nitride and a preparation method thereof, and a wear-resistant coating.

[0006] As one aspect, the present disclosure provides a method for preparing modified boron nitride, comprising: reacting boron nitride with a sulfonic acid (-SO3 - ) The compound with active group molecular chain is subjected to grafting reaction by ball milling to prepare modified boron nitride; wherein the mass ratio of boron nitride to the compound is 1: (0.5-2).

[0007] As another aspect, the present disclosure provides a modified boron nitride obtained by the above-mentioned preparation method, wherein the surface chemical grafting of the boron nitride contains sulfonic acid (-SO3 - )Molecular chain of active groups.

[0008] As yet another aspect, the present disclosure provides an application of modified boron nitride in a wear-resistant coating, wherein the modified boron nitride includes the modified boron nitride obtained by the above-mentioned preparation method or the above-mentioned modified boron nitride.

[0009] As another aspect, the present disclosure provides a wear-resistant coating, wherein the preparation method of the wear-resistant coating comprises: subjecting the modified boron nitride prepared by the above preparation method or the above modified boron nitride to a curing reaction with an aqueous resin emulsion to obtain the wear-resistant coating.

[0010] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0011] The boron nitride is mechanically and chemically exfoliated by high-energy ball milling of macromolecular sodium polystyrene sulfonate and boron nitride. At the same time, polystyrene sulfonic acid molecular chains are chemically grafted onto the surface of the boron nitride. The molecular chains contain a large amount of sulfonic acid (-SO3 - ) active groups. Boron nitride modified with sodium polystyrene sulfonate can effectively reduce the agglomeration of hexagonal boron nitride and improve the dispersibility of hexagonal boron nitride in polymers because of its surface grafted polystyrene sulfonic acid molecular chains. At the same time, the long-chain polystyrene molecular chains can improve the interaction between the modified hexagonal boron nitride and the polymer chains in the wear-resistant coating, and enhance the compatibility of hexagonal boron nitride with the polymer matrix. On the other hand, the number of hexagonal boron nitride flakes after ball milling and peeling is reduced, the specific surface area is increased, and it is easier to enter the friction area, which is conducive to adhesion to the friction pair. It has strong adhesion and is easy to achieve lubrication, reducing the friction coefficient and wear rate of the wear-resistant coating. Moreover, after the surface of boron nitride is grafted with sodium polystyrene sulfonate molecular chains, its molecular chains contain a large number of sulfonic acid groups. Under water lubrication conditions, the negatively charged -SO3 - The group can adsorb hydrated Na by electrostatic interaction + Cations. These hydrated Na + Cationic ions have high load capacity and low shear resistance, which can prevent direct contact of friction pairs, thereby reducing the friction coefficient and wear rate of the wear-resistant coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0014] Figure 1 is a scanning electron microscope image of the sodium polystyrene sulfonate modified boron nitride of the embodiment of the present disclosure;

[0015] Figure 2 is a transmission electron microscope image of the sodium polystyrene sulfonate modified boron nitride according to an embodiment of the present disclosure;

[0016] Figure 3 The effect of different modified boron nitride contents on the friction coefficient;

[0017] Figure 4 The effect of different modified boron nitride contents on the wear rate. DETAILED DESCRIPTION

[0018] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0019] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0020] Boron nitride has good thermal stability, thermal conductivity and chemical inertness, and is a solid lubricant additive with excellent performance. However, it is very easy to agglomerate in the polymer matrix, which not only reduces the mechanical properties of the material, but also causes lubrication failure, which greatly limits the practical application of boron nitride. At present, boron nitride is mainly modified by ball milling, which is characterized by large-scale preparation. The grinding aid is usually small molecules such as amino acids and sucrose. On the other hand, by directly grafting sulfonic acid groups (-SO3 - ), under water lubrication conditions, the negatively charged -SO3 on the friction pair - The group can adsorb hydrated Na by electrostatic interaction + cations, forming a hydrated lubricating layer. These hydrated Na + Cationic ions have high load capacity and low shear resistance, which can reduce friction coefficient and wear. Its wear reduction mechanism is hydration lubrication.

[0021] According to the inventive concept of one aspect of the present disclosure, a method for preparing modified boron nitride is provided, comprising: reacting boron nitride with a sulfonic acid (-SO3 - ) The compound with active group molecular chain is subjected to grafting reaction by ball milling to prepare modified boron nitride; wherein the mass ratio of boron nitride to the compound includes 1: (0.5-2). For example, the mass ratio of boron nitride to the compound is selected from any one of 1: 0.6, 1: 0.8, 1: 1, 1: 1.2, 1: 1.5, and 1: 1.8.

[0022] The preparation method of modified boron nitride provided in the embodiment of the present disclosure comprises grafting a sulfonic acid (-SO3 - ) active group molecular chain, its molecular chain contains a large number of sulfonic acid groups, under water lubrication conditions, the negatively charged -SO3 - The groups can adsorb hydrated cations through electrostatic action. These hydrated cations have high load capacity and low shear resistance, which can prevent direct contact between the friction pairs, thereby reducing the friction coefficient and wear rate of the wear-resistant coating.

[0023] In some embodiments of the present disclosure, the compound includes sodium polystyrene sulfonate; the speed of ball milling is 400-1000 r / min, and the time is 4-12 h. For example, the speed is selected from any one of 436 r / min, 589 r / min, 689 r / min, 798 r / min, 896 r / min, and 987 r / min, and the time is selected from any one of 4.3 h, 5.6 h, 6.8 h, 7.3 h, 8.2 h, 9.6 h, 10.7 h, and 11.8 h.

[0024] According to an embodiment of the present disclosure, a modified boron nitride obtained by the above-mentioned preparation method is provided, wherein the surface chemical grafting of the boron nitride contains sulfonic acid (-SO3 - )Molecular chain of active groups.

[0025] In some embodiments of the present disclosure, the molecular chain includes a polystyrene sulfonic acid molecular chain.

[0026] According to an embodiment of the present disclosure, there is provided an application of modified boron nitride in a wear-resistant coating, wherein the modified boron nitride comprises the modified boron nitride obtained by the above-mentioned preparation method or the above-mentioned modified boron nitride.

[0027] According to an embodiment of the present disclosure, a wear-resistant coating is provided, wherein a method for preparing the wear-resistant coating comprises: subjecting the modified boron nitride prepared by the above-mentioned preparation method or the above-mentioned modified boron nitride to a curing reaction with an aqueous resin emulsion to obtain the wear-resistant coating.

[0028] In some embodiments of the present disclosure, the wear-resistant coating comprises a polymer wear-resistant coating.

[0029] In some embodiments of the present disclosure, in the method for preparing the wear-resistant coating, the aqueous resin emulsion includes one or more of an aqueous polyurethane emulsion or an aqueous epoxy resin emulsion.

[0030] In some embodiments of the present disclosure, in the method for preparing the wear-resistant coating, the weight ratio of the modified boron nitride to the aqueous polyurethane emulsion includes (2-10): (90-98); for example, the weight ratio is selected from any one of 1:99, 3:97, 5:95, 7:93, and 9:91; and / or the weight ratio of the modified boron nitride to the aqueous epoxy resin emulsion includes (5-20): (80-95), for example, the weight ratio is selected from any one of 6:94, 7:93, 9:91, 11:89, 14:86, and 17:83.

[0031] In some embodiments of the present disclosure, in the method for preparing the wear-resistant coating, the solid content of the aqueous polyurethane emulsion includes 30-35%, for example, the solid content is selected from any one of 30.9%, 31.8%, 32.6%, 33.9%, and 34.6%; the pH includes 6-8, and the pH is selected from any one of 6.1, 6.4, 6.7, 7.1, 7.4, and 7.8; and / or the aqueous epoxy resin emulsion includes an aqueous epoxy resin and a curing agent.

[0032] In some embodiments of the present disclosure, in the method for preparing the wear-resistant coating, the solid content of the water-based epoxy resin includes 35% to 42%, for example, the solid content is selected from any one of 35.9%, 36.8%, 37.6%, 38.9%, 39.6%, 40.6%, and 41.9%; the pH includes 6 to 8, for example, the pH is selected from any one of 6.2, 6.5, 6.8, 7.2, 7.5, and 7.9; the curing agent is an aqueous emulsion of an aromatic amine-type epoxy curing agent, wherein the solid content includes 35% to 45%, for example, the solid content is selected from any one of 36.7%, 38.9%, 39.2%, 41.8%, 42.9%, 43.8%, and 44.9%.

[0033] In some embodiments of the present disclosure, the water-based epoxy resin emulsion comprises a water-based epoxy resin (solid content of 35-42%, pH of 6-8) and a curing agent, and the curing agent is an aqueous emulsion of an aromatic amine-type epoxy curing agent (solid content of 40%).

[0034] In some embodiments of the present disclosure, a method for applying sodium polystyrene sulfonate-modified boron nitride is provided, which is obtained by blending the surface chemically modified two-dimensional material boron nitride with an aqueous resin emulsion and further curing the mixture.

[0035] In some embodiments of the present disclosure, the preparation method of sodium polystyrene sulfonate modified boron nitride comprises the following steps: (1) adding boron nitride and sodium polystyrene sulfonate to a high-speed stirrer, premixing for 30 minutes, and obtaining a boron nitride / sodium polystyrene sulfonate premixed filler; (2) pouring the premix in step (1) into a ball mill containing agate balls, placing the ball mill in a ball mill with a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cooling to room temperature, and collecting the product boron nitride / sodium polystyrene sulfonate composite powder. (3) dispersing the above composite powder in an aqueous solution, using a high-speed centrifuge at a centrifugal speed of 10000 rpm, centrifuging for 20 minutes, and then transferring the precipitate obtained by centrifugation to a dialysis bag (molecular weight cutoff 1000 to 14000), placing it in deionized water for dialysis for 7 days, changing the water every other day, and finally freeze-drying to obtain sodium polystyrene sulfonate modified boron nitride.

[0036] In some embodiments of the present disclosure, a method for preparing modified boron nitride by selecting an aqueous polyurethane emulsion comprises the following steps: mixing 2 to 10 parts by weight (for example, selected from any one of 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, and 9 parts by weight) of sodium polystyrene sulfonate modified boron nitride and 90 to 98 parts by weight (for example, selected from any one of 91 parts by weight, 93 parts by weight, 94 parts by weight, 96 parts by weight, and 97 parts by weight) of an aqueous polyurethane emulsion, mechanically stirring for 1 hour, and ultrasonically dispersing for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blended coating, spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2 to 0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 hours to obtain a modified boron nitride / aqueous polyurethane coating.

[0037] In some embodiments of the present disclosure, a method for preparing modified boron nitride by selecting an aqueous epoxy resin emulsion comprises the following steps: mixing 5 to 20 parts by weight (for example, selected from any one of 6 parts by weight, 9 parts by weight, 14 parts by weight, 17 parts by weight, and 19 parts by weight) of sodium polystyrene sulfonate-modified boron nitride and 80 to 95 parts by weight (for example, selected from any one of 81 parts by weight, 83 parts by weight, 87 parts by weight, 91 parts by weight, and 94 parts by weight) of an aqueous epoxy resin; After mechanical stirring for 1 hour and ultrasonic dispersion for 30 minutes, 10 to 20 parts (for example, any one of 11 parts by weight, 15 parts by weight, 17 parts by weight, 18 parts by weight, and 19 parts by weight) of an aqueous emulsion of an aromatic amine epoxy curing agent is added, and the blended coating is sprayed on a 45# steel substrate by a spraying method (spraying pressure 0.2 to 0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and cured at room temperature for 3 hours to obtain a modified boron nitride / waterborne epoxy coating.

[0038] Example A

[0039] Preparation of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0040] The preparation method comprises the following steps:

[0041] (1) adding boron nitride and sodium polystyrene sulfonate into a high-speed mixer and premixing for 30 minutes to obtain a boron nitride / sodium polystyrene sulfonate premixed filler; wherein the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:1.2;

[0042] (2) Pour the premix in step (1) into a ball mill containing agate balls, place the ball mill in a ball mill at a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cool to room temperature and collect the product boron nitride / sodium polystyrene sulfonate composite powder.

[0043] (3) The above-mentioned composite powder is dispersed in an aqueous solution, and centrifuged at a high-speed centrifuge at a speed of 10,000 rpm for 20 minutes. The precipitate obtained by centrifugation is then transferred to a dialysis bag (molecular weight cutoff 1,000 to 14,000), and dialyzed in deionized water for 7 days, with the water being changed every other day. Finally, the product is freeze-dried to obtain boron nitride modified with sodium polystyrene sulfonate.

[0044] (4) Characterize the boron nitride modified with sodium polystyrene sulfonate obtained in step (3). The results are as follows: Figure 1 , Figure 2 shown.

[0045] Figure 1 is a scanning electron microscope image of boron nitride modified with sodium polystyrene sulfonate; Figure 1It can be clearly seen that the surface of the sodium polystyrene sulfonate-modified boron nitride becomes rough and particles are attached to the surface. Figure 2 This is a transmission electron microscopy image of boron nitride modified with sodium polystyrene sulfonate. Figure 2 The characterization of the transmission electron microscopy images further demonstrated that boron nitride modified with sodium polystyrene sulfonate was synthesized.

[0046] Example B

[0047] Preparation of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0048] The preparation method comprises the following steps:

[0049] (1) adding boron nitride and sodium polystyrene sulfonate into a high-speed mixer and premixing for 30 minutes to obtain a boron nitride / sodium polystyrene sulfonate premixed filler; wherein the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:0.5;

[0050] (2) Pour the premix in step (1) into a ball mill containing agate balls, place the ball mill in a ball mill at a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cool to room temperature and collect the product boron nitride / sodium polystyrene sulfonate composite powder.

[0051] (3) The above-mentioned composite powder is dispersed in an aqueous solution, and centrifuged at a high-speed centrifuge at a speed of 10,000 rpm for 20 minutes. The precipitate obtained by centrifugation is then transferred to a dialysis bag (molecular weight cutoff 1,000 to 14,000), and dialyzed in deionized water for 7 days, with the water being changed every other day. Finally, the product is freeze-dried to obtain boron nitride modified with sodium polystyrene sulfonate.

[0052] Example C

[0053] Preparation of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0054] The preparation method comprises the following steps:

[0055] (1) adding boron nitride and sodium polystyrene sulfonate into a high-speed mixer and premixing for 30 minutes to obtain a boron nitride / sodium polystyrene sulfonate premixed filler; wherein the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:0.8;

[0056] (2) Pour the premix in step (1) into a ball mill containing agate balls, place the ball mill in a ball mill at a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cool to room temperature and collect the product boron nitride / sodium polystyrene sulfonate composite powder.

[0057] (3) The above-mentioned composite powder is dispersed in an aqueous solution, and centrifuged at a high-speed centrifuge at a speed of 10,000 rpm for 20 minutes. The precipitate obtained by centrifugation is then transferred to a dialysis bag (molecular weight cutoff 1,000 to 14,000), and dialyzed in deionized water for 7 days, with the water being changed every other day. Finally, the product is freeze-dried to obtain boron nitride modified with sodium polystyrene sulfonate.

[0058] Example D

[0059] Preparation of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0060] The preparation method comprises the following steps:

[0061] (1) adding boron nitride and sodium polystyrene sulfonate into a high-speed mixer and premixing for 30 minutes to obtain a boron nitride / sodium polystyrene sulfonate premixed filler; wherein the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:1.6;

[0062] (2) Pour the premix in step (1) into a ball mill containing agate balls, place the ball mill in a ball mill at a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cool to room temperature and collect the product boron nitride / sodium polystyrene sulfonate composite powder.

[0063] (3) The above-mentioned composite powder is dispersed in an aqueous solution, and centrifuged at a high-speed centrifuge at a speed of 10,000 rpm for 20 minutes. The precipitate obtained by centrifugation is then transferred to a dialysis bag (molecular weight cutoff 1,000 to 14,000), and dialyzed in deionized water for 7 days, with the water being changed every other day. Finally, the product is freeze-dried to obtain boron nitride modified with sodium polystyrene sulfonate.

[0064] Example E

[0065] Preparation of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0066] The preparation method comprises the following steps:

[0067] (1) adding boron nitride and sodium polystyrene sulfonate into a high-speed mixer and premixing for 30 minutes to obtain a boron nitride / sodium polystyrene sulfonate premixed filler; wherein the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:2;

[0068] (2) Pour the premix in step (1) into a ball mill containing agate balls, place the ball mill in a ball mill at a ball milling speed of 400 to 1000 r / min for ball milling reaction, and after ball milling for 4 to 12 hours, naturally cool to room temperature and collect the product boron nitride / sodium polystyrene sulfonate composite powder.

[0069] (3) The above-mentioned composite powder is dispersed in an aqueous solution, and centrifuged at a high-speed centrifuge at a speed of 10,000 rpm for 20 minutes. The precipitate obtained by centrifugation is then transferred to a dialysis bag (molecular weight cutoff 1,000 to 14,000), and dialyzed in deionized water for 7 days, with the water being changed every other day. Finally, the product is freeze-dried to obtain boron nitride modified with sodium polystyrene sulfonate.

[0070] Application of Boron Nitride Modified by Sodium Polystyrene Sulfonate

[0071] Example 1

[0072] (1) 2 parts by weight of the sodium polystyrene sulfonate-modified boron nitride in Example A and 98 parts by weight of an aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0073] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0074] (3) Testing the performance parameters of the modified boron nitride / waterborne polyurethane coating obtained in step (2); wherein the results of the friction coefficient are listed in Figure 3 The results of wear rate are listed in Figure 4 Other performance parameter test results are listed in Table 1.

[0075] Example 2

[0076] (1) 4 parts by weight of the sodium polystyrene sulfonate modified boron nitride of Example A and 96 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0077] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0078] (3) Testing the performance parameters of the modified boron nitride / waterborne polyurethane coating obtained in step (2); wherein the results of the friction coefficient are listed in Figure 3 The results of wear rate are listed in Figure 4 Other performance parameter test results are listed in Table 1.

[0079] Example 3

[0080] (1) 6 parts by weight of the sodium polystyrene sulfonate-modified boron nitride in Example A and 94 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0081] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0082] (3) Testing the performance parameters of the modified boron nitride / waterborne polyurethane coating obtained in step (2); wherein the results of the friction coefficient are listed in Figure 3 The results of wear rate are listed in Figure 4 Other performance parameter test results are listed in Table 1.

[0083] Example 4

[0084] (1) 8 parts by weight of sodium polystyrene sulfonate-modified boron nitride and 92 parts by weight of aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0085] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0086] (3) Testing the performance parameters of the modified boron nitride / waterborne polyurethane coating obtained in step (2); wherein the results of the friction coefficient are listed in Figure 3 The results of wear rate are listed in Figure 4 Other performance parameter test results are listed in Table 1.

[0087] Example 5

[0088] (1) 10 parts by weight of the sodium polystyrene sulfonate modified boron nitride in Example A and 90 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0089] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0090] (3) The performance parameters of the modified boron nitride / waterborne polyurethane coating obtained in step (2) were tested, and the results are shown in Table 1.

[0091] According to the data analysis in Table 1, the following conclusions can be drawn: From the data in Figure 1, it can be seen that all coatings have good adhesion, wear resistance, salt spray resistance and aging resistance.

[0092] Table 1 Test results of performance parameters of modified boron nitride / waterborne polyurethane coatings of Examples 1 to 5

[0093]

[0094]

[0095] Comparative Example 1

[0096] (1) 0 parts by weight of sodium polystyrene sulfonate-modified boron nitride and 100 parts by weight of aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0097] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0098] (3) The performance parameters of the waterborne polyurethane coating obtained in step (2) are tested, wherein the results of the friction coefficient are listed in Figure 3 The results of wear rate are listed in Figure 4 middle.

[0099] The friction performance of Examples 1 to 5 and Comparative Example 1 was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The results are as follows: Figure 3 and Figure 4 shown.

[0100] Based on the above data analysis, the following conclusions can be drawn: pass Figure 3 Effect of different modified boron nitride contents on friction coefficient Figure 4 The influence of different modified boron nitride fractions on the wear rate can be concluded as follows: the friction coefficient and wear rate of modified boron nitride / waterborne polyurethane coating are reduced; the specific reasons are explained as follows: after the surface of boron nitride is grafted with sodium polystyrene sulfonate molecular chains, its molecular chains contain a large number of sulfonic acid groups. Under water lubrication conditions, the negatively charged -SO3 - The group can adsorb hydrated Na by electrostatic interaction + Cations. These hydrated Na +Cationic ions have high load capacity and low shear resistance, which can prevent direct contact of friction pairs, thereby reducing the friction coefficient and wear rate of the wear-resistant coating.

[0101] Example 6

[0102] (1) 6 parts by weight of the sodium polystyrene sulfonate modified boron nitride in Example B and 94 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0103] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0104] The friction performance of the modified boron nitride / waterborne polyurethane coating obtained in step (2) was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The measured friction coefficient was 0.77 and the wear volume was 3.33*10 - 5 mm 3 / Nm.

[0105] Example 7

[0106] (1) 6 parts by weight of the sodium polystyrene sulfonate-modified boron nitride in Example C and 94 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0107] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0108] The friction performance of the modified boron nitride / waterborne polyurethane coating obtained in step (2) was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The measured friction coefficient was 0.68 and the wear volume was 2.14*10 - 5 mm 3 / Nm.

[0109] Example 8

[0110] (1) 6 parts by weight of the sodium polystyrene sulfonate modified boron nitride in Example D and 94 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0111] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0112] The friction performance of the modified boron nitride / waterborne polyurethane coating obtained in step (2) was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The measured friction coefficient was 0.63 and the wear volume was 3.52*10 - 5 mm 3 / Nm.

[0113] Example 9

[0114] (1) 6 parts by weight of the sodium polystyrene sulfonate-modified boron nitride in Example E and 94 parts by weight of the aqueous polyurethane emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous polyurethane blend coating;

[0115] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne polyurethane coating;

[0116] The friction performance of the modified boron nitride / waterborne polyurethane coating obtained in step (2) was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The measured friction coefficient was 0.74 and the wear volume was 5.58*10 - 5 mm 3 / Nm.

[0117] Example 10

[0118] (1) 6 parts by weight of the sodium polystyrene sulfonate modified boron nitride of Example A and 94 parts by weight of an aqueous epoxy resin emulsion were mixed, mechanically stirred for 1 hour, and ultrasonically dispersed for 30 minutes to obtain a modified boron nitride / aqueous epoxy blend coating;

[0119] (2) spraying the blended coating on a 45# steel substrate by a spraying method (spraying pressure 0.2-0.4 MPa, spraying angle 45°, spraying distance 20 cm, nozzle diameter 1 mm), and curing at room temperature for 3 h to obtain a modified boron nitride / waterborne epoxy coating;

[0120] The friction performance of the modified boron nitride / waterborne epoxy coating obtained in step (2) was tested using a UMT friction and wear tester, and the wear volume was observed using a white light diffractometer. The measured friction coefficient was 0.78 and the wear volume was 2.74*10 - 5 mm 3 / Nm.

[0121] The following conclusions can be drawn from the above data analysis : Comparing Examples 3, 6 to 9, it can be seen that when the mass ratio of boron nitride to sodium polystyrene sulfonate is 1:1.2, the coating has the lowest friction coefficient. When the ratio of sodium polystyrene sulfonate to boron nitride is relatively low, due to the low content of sulfonic acid groups grafted on the surface of boron nitride, the dispersion in the polymer matrix is ​​not good, and the hydration effect is also weak, so the friction coefficient is high. When the mass ratio of boron nitride to sodium polystyrene sulfonate is too high, due to the introduction of too many sulfonic acid groups on the surface of boron nitride, the interaction between boron nitride and the matrix is ​​weakened, and it is easy to peel off during the friction process, which also leads to an increase in the friction coefficient of the coating.

[0122] The preparation method of modified boron nitride provided in the embodiment of the present disclosure adopts a high-energy ball milling method to mechanically and chemically exfoliate the boron nitride, and at the same time chemically grafts a polystyrene sulfonic acid molecular chain on the surface of the boron nitride. The molecular chain contains a large amount of sulfonic acid (-SO3 - ) active groups. Boron nitride modified with sodium polystyrene sulfonate can effectively reduce the agglomeration of boron nitride and improve the dispersibility of boron nitride in polymers because of its grafted polystyrene sulfonic acid molecular chains on its surface. At the same time, the long-chain polystyrene molecular chains can improve the interaction between the modified boron nitride and the polymer chains in the wear-resistant coating, and enhance the compatibility of boron nitride with the polymer matrix. On the other hand, the number of boron nitride flakes after ball milling peeling is reduced, the specific surface area is increased, and it is easier to enter the friction area, which is conducive to adhesion to the friction pair. It has strong adhesion and is easy to achieve lubrication, reducing the friction coefficient and wear rate of the wear-resistant coating. Moreover, after the surface of boron nitride is grafted with sodium polystyrene sulfonate molecular chains, its molecular chains contain a large number of sulfonic acid groups. Under water lubrication conditions, the negatively charged -SO3 - The group can adsorb hydrated Na by electrostatic interaction + Cations. These hydrated Na + Cationic ions have high load capacity and low shear resistance, which can prevent direct contact between friction pairs, thereby reducing the friction coefficient and wear rate of the wear-resistant coating, thereby solving the agglomeration problem of boron nitride in polymer wear-resistant coatings.

[0123] This method is simple, efficient and convenient for large-scale industrial production. It not only solves the problem that boron nitride is easy to agglomerate and difficult to disperse in the polymer matrix, but also utilizes the characteristics of the grafted sodium polystyrene sulfonate molecular chain containing a large number of sulfonic acid groups, and utilizes electrostatic adsorption to form a hydrated lubricating layer to avoid direct contact between the friction pairs, thereby further reducing the friction coefficient and wear rate of the wear-resistant coating and increasing the effective service life of the wear-resistant coating.

[0124] The preparation method of the embodiment of the present disclosure is simple and feasible, has strong operability, and can be mass-produced.

[0125] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0126] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A wear-resistant coating, wherein: The preparation method of the wear-resistant coating comprises: subjecting modified boron nitride to a curing reaction with an aqueous resin emulsion to obtain the wear-resistant coating, wherein the aqueous resin emulsion is an aqueous polyurethane emulsion; Wherein, the weight ratio of the modified boron nitride to the aqueous polyurethane emulsion is 6:94; The surface of the modified boron nitride is chemically grafted with polystyrene sulfonic acid molecular chains; The preparation method of the modified boron nitride comprises: performing a grafting reaction between boron nitride and sodium polystyrene sulfonate by ball milling to prepare the modified boron nitride; Wherein, the mass ratio of the boron nitride to the sodium polystyrene sulfonate is 1:1.

2.

2. The wear-resistant coating according to claim 1, wherein: In the preparation method of modified boron nitride, the rotation speed of the ball mill is 400-1000 r / min, and the time is 4-12 h.

3. The wear-resistant coating according to claim 1, wherein: In the method for preparing the wear-resistant coating, The waterborne polyurethane emulsion has a solid content of 30-35% and a pH of 6-8.

Citation Information

Patent Citations

  • Wear-resistant cable and manufacturing method thereof

    CN115044142A